Pengaruh Stimulasi Tugas Terhadap Motivasi dan Pemahaman Membaca Mahasiswa Dengan Rancangan One Shot case study - Yurni, Yurni; Hariati, Febi (Universitas Batanghari Jambi, 2022)
This study seeks to increase intrinsic reading motivation by using situational interest to encourage the development of long-term individual reading motivation. Stimulating tasks are used to increase situational interest. Simultaneously, the researcher provides books on the topic of stimulating tasks to satisfy the curiosity arising from these tasks. Students who have high task stimulation show an increase in reading comprehension after controlling for initial comprehension. Students' reading motivation predicts the level of reading comprehension after controlling for initial comprehension. Task stimulation in reading increases situational interest, which increases long-term intrinsic motivation and reading comprehension.